Carbon emission reduction and reliable power supply equilibrium based daily scheduling towards hydro-thermal-wind generation system: A perspective from China. (15th May 2018) - Xu, Jiuping; Wang, Fengjuan; Lv, Chengwei; Xie, Heping
Highlights: Multi-objective model for a hydro-thermal-wind complementary system is proposed. Trade-offs between carbon emission reduction and reliable power supply is analyzed. 12 scheduling scenarios to handle the wind and hydropower uncertainty are considered. Real case in China to demonstrate the model practicality and efficiency is presented. Abstract: The carbon emission reduction being achieved by Chinese coal combusted electricity generation are critical for global sustainable development and environmental protection. In this paper, to achieve carbon emission reduction and reliable electricity generation, an equilibrium strategy based on a hydro-wind-thermal complementary system under an uncertain environment that fully considers the cooperation of hydro power plants, wind power plants, and coal combusted thermal power plants is proposed as an optimization method. By considering the randomness of seasonal wind speeds, the water flow uncertainty and the fuzziness of coal thermal plant carbon emissions, the complementary model is more scientific and practical than current models. A case study from Bijie City is presented to demonstrate the practicality and efficiency of the optimization model. The results from 12 different wind speed and water flow level scenarios showed that the complementary system provides a superior method to solving the conflicts between carbon emission reduction and reliable electricity generation and therefore could be of great assistance to system operators when scheduling generation.